Note a margine di una nuova edizione dell'Iter di Matthew Paris. - Pitocchelli, Bernardino (Critica del Testo, 2023)
This essay aims to provide a review of the available studies in preparation of the new edition of the Iter de Londinio in Terram Sanctam by Matthew Paris. The author examines textual, iconographic and material aspects of the Iter, considered as exemplary to show the working methodology used for the edition. Through the analysis of some toponyms and legendary material of different kinds, he aims to retrieve some of the sources used in the writing of the itinerary, and at the same time, to reconstruct albeit partially Matthew Paris's ideological horizon.